The relationship between anger, aggression and video gaming - Karl Elí Karlsson 1993- (2019)
Over the years the popularity of video games has grown rapidly and today they play a vital part in adolescents lives. The effects of playing video games have been widely discussed over the past few years. Today the majority of existing studies on this matter have focused on the possible negative consequences of playing video games such as increased aggression. However studies have also shown that it can be beneficial to play video games, as it can enhance creativity. Due to the lack of clarity whether it is video games or confound variables that account for increased anger and aggression the purpose of this study is to examine the impact of video games, sleep, leisure and social activities, and physical and mental health on anger and aggression. The data used in the study was collected by The Icelandic Center for Social Research and Analysis (ICSRA), called Youth in Iceland 2016. Participants were 2,106 Icelandic student in 8th-10th grade. Gender distribution was equal, 50.9% were male and 48.7% were female. The findings indicate that there was a positive association between playing video games, anger and aggression. Furthermore, the findings of the research show that the relationship between video gaming and both anger and aggression, is mediated by sleep and mental health status. Keywords: Video games, anger, aggression, sleep, physical and mental health, leisure and social activities margra ungmenna. Hver áhrif aukinnar tölvuleikjaspilunar eru hefur verið mikið til umræðu undanfarin ár. Flestar rannsóknir hafa beinst að þeim neikvæðu áhrifum sem tölvuleikir gætu haft í för með sér, t.d aukin ýgi. Þó hafa aðrar rannsóknir sýnt fram á möguleg jákvæð áhrif tölvuleikja, t.d að þeir stuðli að auknum sköpunarkrafti. Það er enn óljóst hvort að tölvuleikir einir og sér valdi þessum mögulegu neikvæðu áhrifum, eða hvort að aðrir þættir gætu spilað inn í. Markmið rannsóknarinnar er því að skoða áhrif tölvuleikjaspilunar, svefns, tómstunda- og félagsstarfs, og líkamlegrar og andlegrar heilsu á reiði og ýgi. Rannsóknin ...